Transforming school leadership: A qualitative inquiry into AI-assisted supervision and teacher performance in Indonesian elementary schools - Gugun Gunadi (Journal of Educational Management and Instruction (JEMIN), 2025)
In the era of digital transformation, artificial intelligence (AI) presents new opportunities to enhance educational supervision and teacher performance. However, limited research has explored its practical integration in elementary school contexts, particularly in rural Indonesian settings. This study investigates how AI-assisted educational supervision can support leadership practices and improve teacher performance in elementary schools in Cianjur, West Java. Adopting a qualitative case study design, data were collected from 14 participants, including principals (n=4), vice principals (n=3), senior teachers (n=4), and education office supervisors (n=3), through semi-structured interviews, document analysis, and non-participant observations. Thematic analysis was conducted, with triangulation and member checking to ensure trustworthiness. Findings reveal that participants generally perceive AI (ChatGPT, Canva, Grammarly and LMS) as a beneficial, supportive tool for enhancing fairness, feedback, and supervisory efficiency. Despite limited infrastructure and formal policies, educators creatively utilized tools such as ChatGPT, Grammarly, Google Forms, Zoom, and Canva to simulate AI-supported supervision. A key and unexpected finding was the proactive adaptation of generative AI tools for lesson preparation and performance reporting, even without formal institutional directives. However, challenges such as digital literacy gaps, infrastructure inequities, and cultural resistance emerged as significant barriers. The study indicates the need for policy support, capacity-building, and culturally responsive frameworks to scale AI in educational supervision.